“THE SAVIOR OF THE CITY”: THE CONSTRUCTION OF POLITICAL CAPITAL AND THE DISCURSIVE ENTANGLEMENTS BETWEEN MEDIA AND POLITICS IN GUAYAQUIL - Silva-Torres, Karen; Villarreal Velásquez, José Antonio (Revista de Historia Social y de las Mentalidades, 2021)
From an interdisciplinary perspective that combines conceptual history and media anthropology, this article analyses the discursive entanglements between mass media and politics in the local context of Ecuador at the end of the 20th century. The text asks how the cooperation between the media field and political field contributed to constructing the political capital of León Febres-Cordero, major of Guayaquil, in 1992. Through a detailed examination of the archive, the text shows that the political and media narratives transformed the concepts of public space, citizenship, and authority into key aspects of the political capital of the leader of a political party that has ruled one of the most important cities in the country for almost 30 years.